Epidemiology Of Priority Infectious Diseases In The Interdisciplinary Education System Of Dental Medicine - Doina Azoicai (Romanian Society of Oral Rehabilitation, 2013)
The objectives of medical education aim at ensuring that the information is conveyed accurately to the future generations of doctors, in an updated system, based on interdisciplinarity. The academic structures where the medical education takes place have earned the liberty to assert themselves, becoming an important partner of the health system which offers services whose pertinence is widely acknowledged and having the confirmation of the impact of its actions by complying with all its rights and obligations. The important character of the institutional reform in the field of medical education is to assume the continuity of its actions and to assess whether they lead to the benefits sought after. The curricular changes should observe the current exigencies that govern the medical education within the faculties of medicine, including: transparency, competitiveness and efficiency. The interdisciplinary approach of the epidemiology of infectious diseases is carried out during the didactic process from the faculties of medicine following several directions, outlining: the microbiological characteristics of the pathogen agents involved in the aetiology of the disease; the clinical particularities in the case of studied entities; the structure of the epidemiologic process as well as the concrete measures of general, special and specific prevention that need to be enforced to limit the consequences of the disease on the individual, and especially on the collectivity as a whole. The infectious pathology is of actuality in the integrative educational system of Dental Medicine and the tendency of emergence and re-emergence of infectious diseases creates the premises for a correct and complete formation of the future doctors with regard to the epidemiologic dimension of the phenomena.